Bioresorbable poly(ester-ether urethane)s fromL-lysine diisocyanate and triblock copolymers with different hydrophilic character - Abraham, Gustavo Abel (2006)
Bioresorbable linear poly(ester‐ether urethane)s with different hydrophilic character were synthesized from block copolymers of poly(ϵ‐caprolactone)‐poly(ethylene oxide)‐poly(ϵ‐caprolactone) (PCL‐PEO‐PCL) as macrodiols, and L‐lysine diisocyanate (LDI). A series of PCL‐PEO‐PCL triblock copolymers with different PEO and PCL chain length was obtained by reacting PEO with ϵ‐caprolactone. Polyurethanes were synthesized by reacting the triblock copolymers with LDI in solution using stannous 2‐ethylhexanoate as catalyst. The prepared triblock copolymers and polyurethanes were fully characterized by proton nuclear magnetic resonance spectroscopy, size exclusion chromatography, differential scanning calorimetry, and wide‐angle X‐ray diffraction. Water uptake, hydrolytic stability, and tensile properties of polyurethanes with different composition were evaluated and discussed in terms of the chain length and molecular weight of the polymers and its block components. Water uptake seems to depend on the ethylene oxide unit content of the polyurethane regardless of the triblock structure. Mechanical properties of the synthesized polymers were strongly affected by the molecular weight achieved during polymerization. The use of triblock macrodiols with different hydrophilicity allowed the preparation of a series of polyurethanes having a broad range of properties